1995
DOI: 10.1093/ajcn/61.3.514
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium homeostasis and bone metabolism during pregnancy, lactation, and postweaning: a longitudinal study

Abstract: Ten women were followed serially to determine the effect of stages of reproduction on calcium and bone metabolism. The study periods were nonpregnant nonlactating, the end of each trimester of gestation, 3 mo lactation, and postweaning. Comparisons were with nonpregnant nonlactating status for each individual. Fractional calcium absorption (P < 0.0001) and concentrations of 1,25-dihydroxyvitamin D (P < 0.01) were higher in the second and third trimesters. Total urinary calcium was higher during pregnancy and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
282
4
10

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 393 publications
(325 citation statements)
references
References 2 publications
24
282
4
10
Order By: Relevance
“…However, due to the low rate of exclusive breastfeeding rate in Hong Kong (Chan et al, 2000b) and the long-term follow-up, the present study was limited by small sample size. Other similar studies have also been limited by small sample sizes, with number of lactating subjects ranging from 9 to 26 (Hayslip et al, 1989;Cross et al, 1995;Krebs et al, 1997;Ritchie et al, 1998). This study confirmed previous studies that lactation is associated with a decrease in BMD and this effect is particularly pronounced at the lumbar spine and femoral neck (Kolthoff et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, due to the low rate of exclusive breastfeeding rate in Hong Kong (Chan et al, 2000b) and the long-term follow-up, the present study was limited by small sample size. Other similar studies have also been limited by small sample sizes, with number of lactating subjects ranging from 9 to 26 (Hayslip et al, 1989;Cross et al, 1995;Krebs et al, 1997;Ritchie et al, 1998). This study confirmed previous studies that lactation is associated with a decrease in BMD and this effect is particularly pronounced at the lumbar spine and femoral neck (Kolthoff et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
“…Cross et al (1995) found elevated iPTH but not 1,25(OH) 2 D postweaning compared with lactation whereas Kalkwarf et al (1996) found elevated 1,25(OH) 2 D but not iPTH postweaning compared with postpartum in nonlactating control subjects. Recent findings also suggest that BMD change during lactation is not associated with iPTH, 1,25(OH) 2 D and 25(OH)D. In contrast, prolactin, estradiol and parathyroid hormone related-peptide may be alternative mechanisms associated with bone loss and recovery during and subsequent to lactation (Sowers et al, 1996(Sowers et al, , 1998.…”
Section: Discussionmentioning
confidence: 79%
“…Ca absorption efficiency increases approximately 2-fold during pregnancy in association with increased expression of enterocytic Ca-binding protein (3,67,144) . As with bone resorption, this increase occurs before the third trimester, ahead of peak fetal bone accretion, and is, therefore, likely to be in anticipation of, rather than being driven by, the increased requirement for Ca (145) .…”
Section: Intestinal Absorption and Renal Excretion Of Calciummentioning
confidence: 99%
“…As with bone resorption, this increase occurs before the third trimester, ahead of peak fetal bone accretion, and is, therefore, likely to be in anticipation of, rather than being driven by, the increased requirement for Ca (145) . The increase in 24 h urinary Ca excretion during pregnancy (3,13,67,144) is considered to be due to the combined effects of the increase in intestinal Ca absorption and the higher glomerular filtration rate associated with pregnancy and not to a change in fractional renal Ca reabsorption (3,146,147) . Fasting Ca excretion, corrected for creatinine clearance, is normal or decreased (3,103) .…”
Section: Intestinal Absorption and Renal Excretion Of Calciummentioning
confidence: 99%
See 1 more Smart Citation